The Role of EEG-Based Emotional Feedback in Enhancing the Effectiveness of Tai Chi Sports Programs for Oral Health Promotion - Si Wei (IEEE Access)
The integration of advanced emotion-driven feedback mechanisms, such as EEG-based emotional analysis, represents an innovative approach to enhancing the effectiveness of Tai Chi sports programs tailored for oral health promotion. Traditional oral health strategies, which often rely on educational campaigns and routine reinforcement of hygiene practices, have demonstrated short-term improvements in knowledge and awareness but struggle to sustain long-term behavioral changes, particularly among populations with low health literacy or motivational barriers. These conventional methods lack personalization and dynamic interaction, limiting their ability to engage diverse populations effectively. To address these shortcomings, our framework bridges the gap between conventional approaches and modern neurofeedback methodologies by integrating EEG-based emotional feedback into Tai Chi sports programs. Tai Chi, a mind-body exercise rooted in traditional Chinese medicine, is recognized for its ability to promote both physical and mental well-being through controlled movement, breath regulation, and cognitive focus. The incorporation of real-time emotional monitoring within Tai Chi sessions allows for dynamic adaptation of training content based on participants’ emotional states, fostering deeper engagement, improved stress regulation, and sustained commitment to positive oral health practices. Additionally, the inclusion of gamified elements and culturally relevant adaptations within Tai Chi practice further enhances user interaction, creating a behaviorally sensitive framework that maximizes long-term adherence and effectiveness in diverse communities. This novel approach leverages the holistic benefits of Tai Chi alongside cutting-edge neurofeedback techniques, offering a transformative pathway for enhancing oral health promotion through sports-based interventions.mework that maximizes long-term adherence and effectiveness in diverse communities.